SEMIOTIC ANALYSIS OF ALPHA GENERATION IN TIKTOK CONTENT @MRCI.TV - Rachma Sri Rejeki, Nariswari; Istiqomah (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study examines the application of Generation Alpha in the TikTok video of the @mrci.tv account using Charles Sanders Peirce's semiotic framework. As digital natives, Generation Alpha grew up with meme-based popular culture, global slang, and visual performativity typical of short video platforms. TikTok is positioned to be a space for the production of meaning that shapes generational identity. The research aims to identify the icons, indexes, and symbols that build the image of Generation Alpha and trace the process of audience meaning. Method: The method used was descriptive qualitative with purposive sampling on the three videos with the highest interaction in July 2024. The analysis uses Peirce's triadic model (representation–object–interpretant) accompanied by time triangulation. Results: The results show that @mrci.tv portrays Generation Alpha as expressive, hyperactive, and attached to digital culture. Icons, indexes, and symbols in content form the stereotypes that the audience accepts. The findings confirm that humor and memes are not only entertaining, but also shape generational imagery in public discourse. Novelty: This study contributes to the study of digital semiotics and opens up opportunities for further research on identity construction in social media.